Peculiarities of immune reaction in patients with drug-resistant pulmonary tuberculosis - T. Ye. Kononova; O. I. Urazova; V. V. Novitsky; Ye. G. Churina; M. V. Ignatov (Бюллетень сибирской медицины)
The results of research the cytokine-secretion activity of mononuclear leukocytes, apoptosis and proliferation of lymphocytes for patients with infiltrative pulmonary tuberculosis has been presented in this article. It has been showed that patients with drug-resistant pulmonary tuberculosis had more evident of damages, particularly significant depression of proliferation of lymphocytes, decreased number of cells expressing CD95-receptor as well as disturbance the secretion of immunoregulatory cytokines.